ECVET- ЕВРОПА КАСБИЙ ТАЪЛИМИ УЧУН КРЕДИТ ТИЗИМИНИ ЎЗБЕКИСТОНДА ҚЎЛЛАНИШНИНГ УСЛУБИЙ МАСАЛАЛАРИ - Турениязова, А.И. (SCIENCE and SOCIETY, 2022)
The article discusses the issues of testing and the possibility of further implementation of the European Credit System for Vocational Education and Training (ECVET) in the national education system of Uzbekistan.
Keywords: vocational education; credit; ECVET; learning outcomes; units of learning outcomes